Going passwordless – a case study on the implementation of passwordless at Accenture : How did Accenture implement passwordless, and what lessons can other organizations learn from it? - Aardenburg, Ronan (My University, 2024)
In recent years, passwordless authentication has become an increasingly popular topic in the cybersecurity industry. An increase in the amount of cyberattacks has warranted a need for better authentication methods, and passwordless is perfectly suited for this issue. As one of the first companies in the world, Accenture has implemented passwordless authentication at a large scale. There is a lack of existing research into implementing authentication systems, especially into passwordless authentication. This thesis investigates the implementation of passwordless authentication at Accenture, through interviews with implementation team members, IT service desk members, and ‘regular’ employees, several key lessons for future implementations have been identified. The study has concluded that clear and concise communication is a key factor in an implementation, as end-users are prone to misunderstanding or ignoring important communication. Furthermore, the IT service desk must be involved as a main stakeholder in an implementation, as they have a heavy burden to support the implementation. To address the gaps in existing research, future studies should focus on the IT service desk and conduct additional case studies to increase the knowledge on passwordless authentication.
Keywords: passwordless, authentication, implementation, end-user communication, FIDO2, passkeys